2018
DOI: 10.1371/journal.pone.0206830
|View full text |Cite
|
Sign up to set email alerts
|

Parameters associated with therapeutic response using peritoneal dialysis for therapy refractory heart failure and congestive right ventricular dysfunction

Abstract: BackgroundIn patients with refractory heart failure (HF) peritoneal dialysis (PD) is associated with improved functional status and decrease in hospitalization. However, previous studies did not focus on right ventricular dysfunction as an important pathophysiologic component of cardiorenal syndrome.MethodsIn a prospective cohort study PD was started in 40 patients with refractory right HF (with/without left HF). Refractoriness to conservative therapy was defined as persistent right heart congestion/ascites wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 38 publications
1
14
0
1
Order By: Relevance
“…Only one PD study has focused on patients with right ventricular failure with and without left ventricular dysfunction. In this particular study, patients with extended ascites, higher systolic pulmonary artery pressure, more marked impairment of right ventricular function and tricuspid valve insufficiency, higher residual renal function, and those who could perform PD without assistance benefited most from this therapy [63].…”
Section: Ventricular Function and Pdmentioning
confidence: 85%
See 1 more Smart Citation
“…Only one PD study has focused on patients with right ventricular failure with and without left ventricular dysfunction. In this particular study, patients with extended ascites, higher systolic pulmonary artery pressure, more marked impairment of right ventricular function and tricuspid valve insufficiency, higher residual renal function, and those who could perform PD without assistance benefited most from this therapy [63].…”
Section: Ventricular Function and Pdmentioning
confidence: 85%
“…Two studies have found a relationship between renal dysfunction at baseline and positive outcomes, yet with conflicting results. In the study by Pavo et al [63], patients with treatment success predefined as survival of at least 12 months combined with improved quality of life, a decline in hospitalization days, or both had better kidney function determined by 24-h-GFR and higher urinary volume. However, an association with eGFR was not found.…”
Section: Non-esrd and Pdmentioning
confidence: 99%
“…In a study by Pavo et al [39], patients who had massive ascites, high PAPs, right-sided cardiac failure, tricuspid valve insufficiency, better residual renal function, and who were able to perform PD independently benefited more from PD treatment.…”
Section: Discussionmentioning
confidence: 99%
“…There was no comparator hemodialysis group in either study. Similarly, in a prospective Austrian study of 40 patients initiating PD in the setting of refractory right‐sided heart failure with or without left‐sided heart failure, the one‐year survival rate was 55% and patients reported improved quality of life and/or fewer hospitalization days 19 . Additionally, 4 patients who were initially deemed ineligible for a left ventricular assist device (LVAD) due to severe right heart failure improved sufficiently following PD initiation to qualify for LVAD implantation 19 .…”
Section: Dialysis Modality and Dialysis‐related Treatment Strategies mentioning
confidence: 93%
“…Similarly, in a prospective Austrian study of 40 patients initiating PD in the setting of refractory right‐sided heart failure with or without left‐sided heart failure, the one‐year survival rate was 55% and patients reported improved quality of life and/or fewer hospitalization days 19 . Additionally, 4 patients who were initially deemed ineligible for a left ventricular assist device (LVAD) due to severe right heart failure improved sufficiently following PD initiation to qualify for LVAD implantation 19 . A propensity‐matched retrospective cohort study of dialysis‐dependent HFrEF patients in Taiwan found a lower incidence of hospitalization for heart failure with PD as compared to hemodialysis (19.7 vs 27.6 events per 1,000 patients‐years, respectively), 20 while a recent systematic review summarizing results in 673 patients from 21 observation studies reinforced that peritoneal dialysis is a reasonable option in diuretic‐resistant HFrEF patients with kidney failure, with an annual mortality of approximately 20% across studies 21 …”
Section: Dialysis Modality and Dialysis‐related Treatment Strategies mentioning
confidence: 93%